Analysis of the Use of Learning Media Based on Blogs, Videos and Video Blogs (Vlogs) in Giving a Positive Effect on Learning (Unnes Science Education Journal, 2022)
The use of appropriate learning media will positively influence learning so that learning objectives can be achieved. The purpose of this study was to conduct a literature review on the use of blogs, videos, and video blogs (vlogs) in learning. This research was conducted using a meta-research or meta-analysis approach, namely a search to collect various information by reviewing several research articles in international and national journals relevant to learning media blogs, videos, and vlogs (video blogs). The articles used were published from 2014 to 2021. Based on the sampling criteria, 47 research articles were obtained, including 20 for blog media, 17 for vlog media, and 10 for vlog media. Results show that vlog media has several advantages; besides positively increasing learning motivation, it can also improve learning outcomes, speaking skills, creativity, effectiveness, and efficiency in producing a product, understanding concepts, and learning characters new experiences. The use of vlog media, which has not been widely used for science learning, in this case, chemistry, because it involves several calculation questions, can be used as an introduction or apperception and motivation so that it does not reduce the content and context of the topic and learning objectives.